Research on intelligent home design of internet of things based on ZigBee. (24th February 2021) - Yuan, Jie; He, Yi
With the rapid development of information technology, improving the intelligent level of family life and modern life style is the trend of future development. Based on the analysis of the development of smart home at home and abroad, a smart home system is designed by combining ZigBee wireless sensor network, gateway technology and mobile terminal remote control app. Firstly, the development and relating technologies of ZigBee are discussed. Secondly, the system overall architecture and data outlier analysis are carried out. Thirdly, the routing algorithm of ZigBee is improved based on neighbour table, and corresponding mathematical model is designed. Fourthly, the location algorithm of ZigBee is improved based on RSSI location algorithm and DV-Hop algorithm. Finally, the system performance is tested based on simulation analysis, results show that the proposed intelligent home system has better performance.